The origins of white power music: the co-opting of punk and Oi! by a parasitical social movement - Windle, James (Deviant behavior, 2025)
This paper challenges the common portrayal of White Power music as evolving from, or being an element of, Oi! punk. The paper traces the histories of White Power music and Oi!, and analyses a sample of 268 Oi! songs for racist or fascist lyrics. It shows that, while some Oi! artists and audience members were involved in far-right activism, the subculture was not itself fascist or overtly racist. Many of those involved in Oi! took action against racism and far-right movements, and almost no songs included racist lyrics. The paper proposes two arguments. First, drawing from Worley, media and scholarly portrayals of Oi! as racist or fascist may represent the demonization of the working-class. Second, that White Power co-opted elements of Oi! does not mean that White Power music emerged from Oi!. Rather it likely emerged from first-wave punk at roughly the same time as Oi!. The central argument being that the White Power music scene, and the far-right more generally, is parasitical. It feeds upon the resources of larger scenes and subcultures, often harming them in the process.